Time up and go en pacientes con Parkinson - Zuñiga España, Adriana Patricia (2023)
ABSTRAC The research was carried out through a documentary bibliographic review with the objective of analyzing the effectiveness of the Time up and go test in patients with Parkinson's as part of the process to improve their stability, gait balance and strength of the lower limbs; evidencing the importance of the test as a physiotherapeutic treatment applied in this population. Parkinson's is a pathology with progressive characteristics in the disorder and degeneration of certain segments of the brain and the central nervous system, which is why it is associated with different motor signs and symptoms. For this reason, physiotherapy intervenes with the objective of avoiding the continuous progressions of the disease. Veracity information was collected from different sources of scientific studies among them; Scielo, Pubmed, Google Scholar, PEDro, Elsevier, ScienceDirect, Cochrane, Dialnet; identifying 76 articles and through methodological validation, 35 scientific articles were selected that met the requirements of the Physitherapy Evidence Database (PEDro) scale, thus allowing to find information that supports the objectives of the research. The investigation deduces that the TUG test demonstrates its effectiveness as a predictor of falls, stipulating the patient referred by Parkinson's on a test basis in the gait phase and evaluating the time it takes to complete this action, thus assessing the degrees of complication that manifests itself in each item. Therefore, its application and use of the test is recommended due to the positive effects it presents. Keywords: Parkinson's, Timed up and go, balance, older adults, instability